Mycotic loadsâ determination of non-sterile pharmaceuticals in lagos state and 16S rDNA identification of the fungal isolates - Oyebanji, Elizabeth Olawumi; Adekunle, Adedotun Adeyinka; Coker, Herbert Alexander B.; Adebami, Gboyega Ebenezer (Journal of Applied Pharmaceutical Research, 2018)
Pharmaceuticals are medicinal products used in the prevention, treatment, and diagnosis of diseases. As such, the presence of microorganismsâ especially fungal toxins can reduce or eliminate the products therapeutic activity and constitute a potential danger to patient health. This study attempts to determine the fungal loads of liquid preparation used as medication in Lagos State and its environs and identify the fungal isolates. 252 different types of oral liquid drugs (200syrups and 52 suspensions) which included paracetamol syrup, cough syrup and antibiotics suspension manufactured in five different pharmaceutical industries in Nigeria were methodically sampled and analyzed for fungi contamination using standardized method. The isolated fungi were identified using morphological characterization as well as 16SrDNA sequencing. 13% of the sampled syrups were found to be contaminated with fungi where thecolony forming units for paracetamol syrup, cough syrup and antibiotics suspension ranges from 2.0x101 - 9.6Ã104; 1.0x102- 7.5x104 and 1.0x101- 8.8Ã104cfu/ml respectively while87% yielded no growth.Thirteen (13) morphologically different species of fungi were identified which included Aspergillus niger strains, A. tamari strains, A. japonicas, A. flavus, A. awamari, A. ellipticus, A. tubingensis, Meyerozyma aaribbica, Candida carpophila and  Eurotiomycetes spp, The presence of microorganisms in oral liquid samples might explain the treatment complicacy of the diseased children. Therefore, microbiological quality of such drugs is thus suggested.